From organizational capabilities to corporate performances: At the roots of productivity slowdown - Stefano Costa; Stefano De Santis; Giovanni Dosi; Roberto Monducci; Angelica Sbardella; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper is one of the first attempts at empirically identifying organisational capabilities - in this work concerning Italian firms. Together, it proposes new evidence on the link between capabilities and economic performances. In order to do so, we employ the Indagine Multiscopo del Censimento Permanente delle Imprese (IMCPI), a survey carried out by the Italian Statistical Office (ISTAT) in 2019, covering the three-year period 2016-2018, addressing a wide range of organizational characteristics including various organizational routines, human resource management, internationalisation strategies and many others. Our contribution is threefold: first, we aim at detecting what practices and combinations of them result in underlying different capabilities; second, we propose a taxonomy of the production system, both at firm- and sector-level based on the mapping of such capabilities, third we study the performance outcomes of different capability-taxa in terms of productivity and employment growth.
Keywords: D21; D22; D83; J24; J53; 330; Organizational capabilities; productivity slowdown; employment growth; learning